Pengaruh Pemberian Kompos TrichoazollaDan Pupuk Npk Mutiara (16:16:16) Terhadap Pertumbuhan Dan Produksi Tanaman Jagung Manis (Zea mayssaccarata Sturt) - M. Khairul Mustofa; Jurnawaty ' Sofjan; Edison ' Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This reserch was aimed to know ifluence of. Compost Trichoazolla and pearl NPK Mutiara (16:16:16) the growth and prodution of swet corn. The research was conducted at the experiment staion of Faculty of Agriculture University of Riau from agustus 2015 to november 2015. This reseach is an experimental with combination.The parameters measured were plant height (m), stem diameter (cm), the time appears male and female flowers (HST), leaf area (cm2), harvesting (HST), cob diameter (cm), weight cobs berkelobot per plot (kg), weight per cob without husk (g), the length of the cob without husk (cm) and plant dry weight (g). Combination komposTrichoazolla9 tonnes / ha with NPK fertilizer 200 kg / ha give cob production berkelobot high in sweet corn with the acquisition results of 9.00 kg / 6m2 or (15,00ton / ha), compared with those without compost Trichoazolla and without NPK yaitu5,16 kg / 6m2 or (8.60 tonnes / ha), it means having the difference of 6.4 ton / ha (42.66%). Keywords: sweet corn, Trichoazolla Compost and fertilizer NPK (16:16:16)